Structural constraints and patient agency in diabetes self-management: a critical case study in a primary healthcare center in Indonesia - Yulia, Yulia; Abigail, Wendy; Willis, Eileen; Shifaza, Fathimath (Universitas Airlangga, 2025)
Introduction: Effective self-management is essential for individuals with Type 2 Diabetes Mellitus (T2DM), yet patients in Indonesia often encounter persistent barriers. This study explores patients’ perspectives on the challenges they face as well as the perceived supports available within the primary healthcare system. Methods: A qualitative case study approach, based on Yin’s methodology, was employed. Guided by Habermas’s theory of communicative action and Honneth’s theory of recognition, data were collected through in-depth interviews with 14 patients, 28 clinical observations of patient–provider encounters, and one focus group with five healthcare professionals. Participants were recruited from a suburban primary healthcare center in Indonesia using purposive sampling. Reflexivity and field notes were maintained throughout the data collection process. Data were analyzed using thematic qualitative analysis. Triangulation across data sources helped enhance credibility and trustworthiness. Results: Five key themes emerged: (1) Medical dominance in care provision, (2) Communication gaps, (3) Regulation-centered care, (4) Care quality, and (5) Patient self-empowerment. These themes reveal systemic, structural, and interpersonal barriers that constrain effective diabetes self-management in primary care. Conclusions: Understanding the lived experiences of patients with T2DM is critical to informing practice and policy. To overcome these barriers, a shift toward patient-centered care, improved communication, and more inclusive support systems is essential within Indonesia’s healthcare system.